Business Communication in the Sustainability of Belitong Geopark to Economic Growth of Tanjungpandan Community - Rizky Ramadhani Arsyah Putra; Prahastiwi Utari; Sudarmo (UIR Press, 2024)
The Belitong Geopark, located in Tanjungpandan is one of the geopark areas that has extraordinary natural potential. The sustainability of the Belitong Geopark has become a concern in recent years, with efforts to utilize the geopark's potential to support the economic growth of local communities that have not felt a significant economic impact. At the level of business communication studies, we see that there are barriers to effective communication with the resulting economic implications. The methods of this study are observation and literature review. The data that has been collected is then analyzed using Em Griffin's semiotic analysis. The results showed that the sustainability of the Belitung Geopark has a positive influence on the economic growth of the Tanjungpandan community. The increase in Tanjungpandan community income is driven by increased tourist visits to Geopark Belitung. The increase in employment of the Tanjungpandan community is driven by the increase in economic activities related to Belitung Geopark, such as tourism, trade, and services. The increased welfare of the Tanjungpandan community is driven by increased income and employment.